The Practice of Primary Eye Care by Optometrists Worldwide - A Systematic Literature Review - Muthiah, Prema; Sharanjeet-Kaur, Sharanjeet; Hairol, Mohd Izzuddin; Mohamed Akhir, Saadah; Narayanasamy, Sumithira (IIUM Medical Journal Malaysia, 2025)
Primary eye care involves detecting and managing conditions that cause preventable blindness, as well as diagnosing and treating eye diseases. Optometrists play a central role in primary eye care, yet their scope of practice and challenges vary globally. This systematic review was conducted to examine the roles, scope and challenges faced by optometrists in their practices. The systematic search was performed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines using a registered review protocol. An electronic search of PUBMED, PubMed Central (PMC), Scopus, EBSCO, OVID, and Web of Science (WoS) was conducted between February and September 2022. Two reviewers independently screened and extracted eligible studies. Eleven publications met the inclusion criteria; 10 cross-sectional studies and one retrospective study. Extracted data focused on structural aspects of care delivery, including instrumentation, procedures, services, management, referral pathways, and training. The scope of practice varied widely, ranging from refraction to advanced clinical management, including therapeutic interventions. Standards of optometric practice in several settings extended well beyond refraction and dispensing, incorporating disease management and collaborative care. Optometrists are capable of delivering comprehensive primary eye care that extends beyond basic refractive services. Harmonising educational standards and implementing enabling policies can empower optometrists to work to the full extent of their training, thereby improving access to eye care services and reducing strain on general healthcare systems.